Scalable deoxygenative alkynylation of alcohols via flow photochemistry - Xu, Pin; Ma, Cong (Communications chemistry, 2024)
Internal alkynes are often contained in bioactive pharmaceuticals and crucial intermediates in material sciences, yet their production methods are often limited and challenging, necessitating the development of more efficient and versatile synthetic routes. Here we report a method of deoxygenative alkynylation of alcohols via flow photochemistry. Formation of N -heterocyclic carbene-alcohol adducts undergoes oxidation by a photocatalyst, generating alkyl radicals. These radicals are subsequently trapped by an alkynylation agent, yielding the desired alkyne. Compared to batch reactions, the strategy using flow photochemistry is practical and efficient to complete the reaction in relatively short time with good yields. A wide range of functional groups were tolerated. The broad application of this method for alkyne synthesis in industry settings is anticipated, supported by the potential in late-stage functionalization of biomolecules and gram-scale synthesis. Internal alkynes are often contained in bioactive pharmaceuticals and crucial intermediates in materials science, yet their production methods are often limited and challenging. Here, the authors develop a practical and efficient method for the visible-light-promoted deoxygenative alkynylation of alcohols via flow photochemistry, utilizing N -heterocyclic carbenes to activate alcohols.